2019
DOI: 10.1017/aee.2019.12
|View full text |Cite
|
Sign up to set email alerts
|

From Thoughts to Actions: The Importance of Climate Change Education in Enhancing Students’ Self-Efficacy

Abstract: The relation between the understanding and belief of the site-specific dangers of climate change and the behaviour that individuals take to mitigate their impacts was assessed to investigate the psychological antecedent to pro-environmental behaviour; a necessity to mitigate anthropogenic climate change at the individual level. A quantitative cross-sectional design was employed to measure beliefs and behaviour of university students. Correlation was measured between the belief in one’s ability to affect change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…Viewed differently, students who have lower levels of science literacy are less likely to believe in their capacity to understand and resolve climate change-related issues, which in turn could reduce their motivation to engage in household energy conservation. This finding was consistent with previous studies showing that science literacy promotes climate change knowledge (Jordan et al, 2019) and that the role of sense of efficacy increases people's conservation behaviors (Martinez Gonzalez & Reynolds-Tylus, 2021;Muroi & Bertone, 2019). Furthermore, the present study provided support for the proposition of Social Cognitive Theory (Bandura, 1977(Bandura, , 1986 which emphasized that knowledge alone cannot sufficiently activate behavior and that tapping on the learners' sense of efficacy is critical.…”
Section: Discussionsupporting
confidence: 91%
“…Viewed differently, students who have lower levels of science literacy are less likely to believe in their capacity to understand and resolve climate change-related issues, which in turn could reduce their motivation to engage in household energy conservation. This finding was consistent with previous studies showing that science literacy promotes climate change knowledge (Jordan et al, 2019) and that the role of sense of efficacy increases people's conservation behaviors (Martinez Gonzalez & Reynolds-Tylus, 2021;Muroi & Bertone, 2019). Furthermore, the present study provided support for the proposition of Social Cognitive Theory (Bandura, 1977(Bandura, , 1986 which emphasized that knowledge alone cannot sufficiently activate behavior and that tapping on the learners' sense of efficacy is critical.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, the prior knowledge in climate change, which is an important predictor of people’s perception of climate change ( Aksit et al, 2018 ), should be controlled. This concern, however, might be minimal, as previous work found that there were no significant differences in the level of climate change awareness between Westerners and Asians ( Muroi and Bertone, 2019 ). Finally, the current research did not explore whether the difference in perception of future climate change induced by dialectical beliefs would actually lead to some downstream consequences.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, the present study suggests that cultivating both parents' and adolescents' familiarity with climate change may result in positive intergenerational transmission of pro-environmental behaviors. Therefore, one valuable implication is that formal and informal education programs on climate change (Muroi & Bertone, 2019) should be conducted for different generations, including parents and adolescents. The content of a climate change educational program may cover various aspects of climate change, such as policy, knowledge, and strategies to adapt (Muroi & Bertone, 2019).…”
Section: Practical and Policy Implicationsmentioning
confidence: 99%